Human–climate interaction during the Early Upper Paleolithic: testing the hypothesis of an adaptive shift between the Proto-Aurignacian and the Early Aurignacian - Banks, William E. (2018)
The Aurignacian technocomplex comprises a succession of culturally distinct phases. Between its first two subdivisions, the Proto-Aurignacian and the Early Aurignacian, we see a shift from single to separate reduction sequences for blade and bladelet production, the appearance of split-based antler points, and a number of other changes in stone tool typology and technology as well as in symbolic material culture. Bayesian modeling of available (14)C determinations, conducted within the framework of this study, indicates that these material culture changes are coincident with abrupt and marked climatic changes. The Proto-Aurignacian occurs during an interval (ca. 41.5-39.9 k cal BP) of relative climatic amelioration, Greenland Interstadials (GI) 10 and 9, punctuated by a short cold stadial. The Early Aurignacian (ca. 39.8-37.9 k cal BP) predominantly falls within the climatic phase known as Heinrich Stadial (HS) 4, and its end overlaps with the beginning of GI 8, the former being predominantly characterized by cold and dry conditions across the European continent. We use eco-cultural niche modeling to quantitatively evaluate whether these shifts in material culture are correlated with environmental variability and, if so, whether the ecological niches exploited by human populations shifted accordingly. We employ genetic algorithm (GARP) and maximum entropy (Maxent) techniques to estimate the ecological niches exploited by humans (i.e., eco-cultural niches) during these two phases of the Aurignacian. Partial receiver operating characteristic analyses are used to evaluate niche variability between the two phases. Results indicate that the changes in material culture between the Proto-Aurignacian and the Early Aurignacian are associated with an expansion of the ecological niche. These shifts in both the eco-cultural niche and material culture are interpreted to represent an adaptive response to the relative deterioration of environmental conditions at the onset of HS4.